Study of microclimatic conditions under different environments in wheat crop (MAUSAM, 1996)
An experiment was cunducted to study the wheal microclimate for higher grain yield production at research farm of Hisar 'Agriculture’ University (HAU). Profiles of temperature relative humidity, leaf temperature leaf wetness wind speed were measured in the crop canopies of different sowing treatments. Higher air temperatures and lower soil moisture were observed during reproductive phase under delayed sowings. Albedo varied between 0.19 and 0.23. Test weight decreased with delay in sowing time. Sowing of wheat between 31 October and 14 November produced statistically higher yield under favourable microclimate conditions at dirrerent phenophases.